1998
DOI: 10.1159/000015869
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery and Social Outcome after Cerebral Infarction in Young Adults

Abstract: This study was designed to assess the return to work, the poststroke depression and the quality of life after a cerebral infarction in young adults and was conducted on 71 consecutive young patients (aged 15–45 years) affected by a cerebral infarct who were hospitalized for the first time and discharged at least 1 year before the study. Data about risk factors, etiology, side and territory of stroke, social characteristics of the patient (age, sex, profession, educational level, family situation), poststroke s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
111
2
12

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 43 publications
11
111
2
12
Order By: Relevance
“…According to these scales, in the long-term followup even more than 70%-80% of the patients report no significant problems for daily activities (MRS = 0-2; IB = 100), about 10%-20% report moderate handicaps (MRS = 3), and only about 10% report major handicaps and residual dependency after ischemic stroke (MRS score higher than 3 and/or BI score less than 90) [12,30,41].…”
Section: Long-term Functional Deficitsmentioning
confidence: 99%
“…According to these scales, in the long-term followup even more than 70%-80% of the patients report no significant problems for daily activities (MRS = 0-2; IB = 100), about 10%-20% report moderate handicaps (MRS = 3), and only about 10% report major handicaps and residual dependency after ischemic stroke (MRS score higher than 3 and/or BI score less than 90) [12,30,41].…”
Section: Long-term Functional Deficitsmentioning
confidence: 99%
“…One study showed that one in four patients required adaptation of the job (9). Predictors for not returning to work include high age, female gender, stroke in the left cerebral hemisphere, greater level of hemiplegia, lower functional level (ADL) and impaired cognitive capacity.…”
Section: Evidencementioning
confidence: 99%
“…Reikia pabrėžti, kad depresiją diagnozuoti sudėtinga, jei yra tokių sutrikimų, kaip afazija, anozognozija ir kitų poinsultinių kognityvinių sutrikimų (44). Nustatyta, kad poinsultinė depresija dažnai pasireiškia jauniems pacientams (45,46). Tačiau vyresnio amžiaus pacientai gali būti labiau linkę į depresiją dėl funkcinių ir kognityvinių sutrikimų, buvimo gydymo įstaigose, socialinės pagalbos stokos (39).…”
Section: Kiti Klinikiniai Ir Funkciniai Poinsultinės Depresijos Veiksunclassified
“…J. P. Neau ir kt. atliko tyrimą, siekdami įvertinti jaunų žmonių grįžimą į darbą, poinsultinę depresiją ir gyvenimo kokybę persirgus GSI (45). Į tyrimą įtrauktas 71 pacientas 15-45 metų amžiaus, patyręs GSI, pirmą kartą hospitalizuotas ir išrašytas iš ligoninės bent vieneri metai iki tyrimo.…”
Section: Kiti Klinikiniai Ir Funkciniai Poinsultinės Depresijos Veiksunclassified
See 1 more Smart Citation